2016
DOI: 10.1039/c6ee01109h
|View full text |Cite
|
Sign up to set email alerts
|

Versatile nanoporous bimetallic phosphides towards electrochemical water splitting

Abstract: Nanoporous bimetallic (Co1−xFex)2P phosphides with tuneable Co/Fe ratios exhibit versatile catalytic activities for highly efficient electrochemical water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
326
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(346 citation statements)
references
References 50 publications
(55 reference statements)
10
326
1
Order By: Relevance
“…Note that samples with lower Fe content show higher crystallinity. [39] As shown in Figure 4a, XPS analysis of the Co 1-x Fe x WO 4 ÀCNT exhibits the presence of the Co, Fe, C, O and W. Figure 4b and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 4c demonstrate the presence of Co 2 + , Co 3 + , Fe 2 + and Fe 3 + . Furthermore, the (120) peak showed in XRD patterns ( Figure S2 The chemical composition and electronic structure of the Co 1-x Fe x WO 4 ÀCNT composites were examined by X-ray photoelectron spectroscopy (XPS, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Note that samples with lower Fe content show higher crystallinity. [39] As shown in Figure 4a, XPS analysis of the Co 1-x Fe x WO 4 ÀCNT exhibits the presence of the Co, Fe, C, O and W. Figure 4b and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 4c demonstrate the presence of Co 2 + , Co 3 + , Fe 2 + and Fe 3 + . Furthermore, the (120) peak showed in XRD patterns ( Figure S2 The chemical composition and electronic structure of the Co 1-x Fe x WO 4 ÀCNT composites were examined by X-ray photoelectron spectroscopy (XPS, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…As such, Lou and co‐workers synthesized porous nickel phosphides nanoplates with carbon coating from Ni–Ni Prussian blue analog nanoplates and further confirmed that the obtained nickel phosphide possessed exceptional electrocatalytic OER activity superior to nickel oxide/hydroxide with similar morphology . To date, several efficient strategies including making porous nanostructures, adopting multimetallic catalysts by taking advantage of synergistic metal–metal interactions, and introducing carbon materials as favorable supports have been established to rationally engineer their structures and composition to further enhance OER performance. For example, our group focused on these critical issues and developed some promising bimetallic phosphides with porous nanostructures, such as highly ordered mesoporous CoNiP with large pore size and metal–organic framework (MOF)‐derived cobalt‐based bimetallic phosphide .…”
Section: Introductionmentioning
confidence: 94%
“…

catalysts with low-cost and earth-abundant materials. [10][11][12][13] Most state-of-the-art water splitting catalyst researches have been focused on the development of nonprecious metal catalysts that are competitive to precious metals. Nevertheless, practical utilization of these electrodes in an integrated electrolysis device has been hindered since the HER and OER catalysts usually require very different pH values in order to produce long lifetimes and high activities.

…”
mentioning
confidence: 99%